Microsaccades: Empirical Research and Methodological Advances - Susana Martinez-Conde; Ralf Engbert; Rudolf Groner (Journal of Eye Movement Research)
Recent technical developments and increased affordability of high-speed eye tracking devices have brought microsaccades to the forefront of research in many areas of sensory, perceptual, and cognitive processes. The present thematic issue on “Microsaccades: Empirical Research and Methodological Advances” invited authors to submit original research and reviews encompassing measurements and data analyses in fundamental, translational, and applied studies.